Treatment decision in adult patients with class III malocclusion: surgery versus orthodontics - Sara Eslami; Jorge Faber; Ali Fateh; Farnaz Sheikholaemmeh; Vincenzo Grassia; Abdolreza Jamilian (SpringerOpen, 2018)
Abstract Background One of the most controversial issues in treatment planning of class III malocclusion patients is the choice between orthodontic camouflage and orthognathic surgery. Our aim was to delineate diagnostic measures in borderline class III cases for choosing proper treatment. Methods The pretreatment lateral cephalograms of 65 patients exhibiting moderate skeletal class III were analyzed. The camouflage group comprised of 36 patients with the mean age of 23.5 (SD 4.8), and the surgery group comprised of 29 patients with the mean age of 24.8 years (SD 3.1). The camouflage treatment consisted of flaring of the upper incisors and retraction of the lower incisors, and the surgical group was corrected by setback of the mandible, maxillary advancement, or bimaxillary surgery. Mann-Whitney U test was used to compare the variables between the two groups. Stepwise discriminant analysis was applied to identify the dentoskeletal variables that best separate the groups. Results Holdaway H angle and Wits appraisal were able to differentiate between the patients suitable for orthodontic camouflage or surgical treatment. Cases with a Holdaway angle greater than 10.3° and Wits appraisal greater than − 5.8 mm would be treated successfully by camouflage, while those with a Holdaway angle of less than 10.3° and with Wits appraisal less than − 5.8 mm can be treated surgically. Based on this model, 81.5% of our patients were properly classified. Conclusions Holdaway H angle and Wits appraisal can be used as a critical diagnostic parameter for determining the treatment modality in class III borderline cases.